Technical skills testing of elite slalom canoeists as a predictor of competition performance - Balas, J.; Busta, J.; Bilý, M.; Martin, A. (International Journal of Performance Analysis in Sport, 2020)
The objective of the current study was to assess the reliability of paddling tests involving pivot turns and their relationship to performance level in elite slalom canoeists. Eighteen elite (national level, N = 9) and high performing elite (HPE - international level, N = 9) slalom canoeists performed timed paddling tests with a different number of pivot turns over progressively longer distances (3 x 40 m, 80 m, 200 m). The tests provided high test-retest reliability over time (ICC = ~0.9, CV = ~2%). HPE canoeists were faster in all tests than elite canoeists, however the largest differences were found over 200 m with 10 pivots (- 8.7 s, P < 0.001, Hedges` g = 1.87). The time of pivoting on their preferred side was similar between elite and HPE canoeists (? 0.2 s, P = 0.162, g = 0.62); however, pivoting on their non-preferred side was significantly faster (- 0.6 s, P = 0.004, g = 1.44) in HPE canoeists. The results showed that paddling tests with simple technical elements clearly distinguished HPE from elite slalom paddlers. The paddling test over 200 m predicted best the performance level and is suitable for training practice in elite slalom canoeists.